2020
DOI: 10.1016/j.enconman.2019.112444
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics evaluation of mono and hybrid nano-enhanced phase change materials (NePCMs) for thermal management of microelectronics

Abstract: Efficient, clean and quiet thermal management has become a vital challenge in for cooling of electronic devices. To enhance the capability and efficiency of passive thermal management, novel composite materials have been designed by the combination of graphene nanoplatelets (GNPs), multiwall carbon nanotubes (MWCNTs), aluminium oxide (Al 2 O 3 ) and copper oxide (CuO) dispersed in the RT-28HC used as a phase change material (PCM). The series of mono and hybrid nano-enhanced phase change materials (NePCMs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 63 publications
1
51
0
Order By: Relevance
“…With the development of nanotechnology, the heat and mass transfer in nanoconned systems such as nanofluid [5,6] and nano-composites brings novel insight for energy conversion and storage [7,8] which make a contribution in thermal management applications. The thermal energy storage (TES) systems based on heat storage materials have been used extensively for energy conversion, storage and transportation in thermal management applications of electronic devices, photovoltaic (PV) modules, Li-ion batteries systems etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of nanotechnology, the heat and mass transfer in nanoconned systems such as nanofluid [5,6] and nano-composites brings novel insight for energy conversion and storage [7,8] which make a contribution in thermal management applications. The thermal energy storage (TES) systems based on heat storage materials have been used extensively for energy conversion, storage and transportation in thermal management applications of electronic devices, photovoltaic (PV) modules, Li-ion batteries systems etc.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there exists two major factors that cause the enhanced phenomenon of thermal conductance within the NCPCMs. Firstly, higher thermal conductivity of the nanoparticles and secondly the motion of the nanoparticles in NCPCMs in liquid-phase which causes a quasi-convection phenomenon[29,8].…”
mentioning
confidence: 99%
“…Industrialists have tried to miniaturize electronic systems while increasing power density, especially for high performance chips. In fact, the miniaturization of electronic components causes an increase in their working temperature and subsequently the challenge of cooling them 1 . To overcome this challenge, phase change materials (PCMs) are integrated in heat sinks for latent heat storage 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation can be overcome by adding nanoparticles inside the PCM in order to improve the thermal conductivity of the base material. Consequently, this technique was the concern of many researchers to reveal the effect of nanoparticles insertion on the thermal behavior of PCM‐based heat sinks 1 . Faraji et al 13 reported a computational investigation of the solid‐liquid transition in a rectangular heat sink filled with copper nanoparticles and PCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation